Influência dos sistemas nanoestruturados na fotoestabilidade e na atividade antioxidante dos compostos fenólicos eugenol, isoeugenol e dehidrodieugenol - Reis, Marinice Martins (2012)
There is a great interest in the study of antioxidants, mainly due to the findings on the effect of radicals in the body. These radicals are needed in many biological processes, but also may be related to processes harmful to our body, such as oxidative stress, which is associated with diseases such as neurodegenerative and cardiovascular diseases, and aging. The phenolic compounds eugenol, isoeugenol and dehydrodieugenol are phenylpropanoids that have properties antibacterial, anesthetic, analgesic, antiallergic and anti-inflammatory, and antioxidant properties, preventing oxidative damage cumulative character. To better understand the behavior of these antioxidants, this study aimed to evaluate the antioxidant activity of eugenol, isoeugenol and dehydrodieugenol against the 1,1-diphenyl-2-picrylhydrazyl radical (DPPH), as well as the radical scavenging activity of these compounds front of the hydroxyl radical (photochemically generated from the decomposition of hydrogen peroxide), prepare nanocarrier with different structural organizations (nanocapsules and nanoemulsions), and verify the ability of these nanostructures to increase the photostability under UV-C compared to the free compounds in solution in the presence and absence of hydroxyl radical (HO ). The dispersion of nanocapsules (NC) and nanoemulsions (NE) were prepared by the method of interfacial deposition of preformed polymer (poly-ε-caprolactone) and spontaneous emulsification, respectively. All formulations presented high encapsulation efficiency, nanometric size, low polydispersity index, negative zeta potential and acid pH values, remaining stable after 7 of storage months. In the kinetic study of the photodecomposition, the compounds showed the following stability (in the absence of the radical HO ): eugenol > dehydrodieugenol > isoeugenol. The nanostructured formulations antioxidants promoted the protection against UV-C photodegradation when compared to a hydroethanolic solution. The increased stability NC compared to the free solution can be attributed to the high absorption of polyester poly-ε-caprolactone in the UV-C. In the presence of HO radical, the dehydrodieugenol was antioxidant the most active antirradicalar, followed by eugenol and isoeugenol. Antioxidants encapsulated in nanocapsules and nanoemulsions have a prolonged radical scavenging activity compared with the solution of eugenol and its derivatives. Cell viability test shows that the nanostructured systems (NC and NE) were not toxic for antioxidant concentration at up to 1mg mL-1. This low cytotoxicity of the samples indicates that the nanocapsules and nanoemulsions prepared in this work may be considered favorable substrate for viable cell.